Watershed Governance for Food Security in the Sio River Basin: A Paradox of Kenya’s Devolution System - Namenya Daniel Naburi; John Obiri; Edward Mugalavai (Budapest International Research and Critics University, 2020)
Institutional and political inefficiencies in Sub-Saharan Africa hinder the implementation of Integrated Water Resource Management approaches. In Kenya, decentralization as a political and institutional tool was designed to strengthen the mandate of county governments and grassroots stakeholders in river basin management to bolster food sector. However, it has been easier for the central government to decentralize powers to the county governments than to strengthen county watershed management framework. To address this paradox, this study examined the effectiveness of watershed governance for sustainable food security in the Lower Sio River Basin of Busia County in Kenya. Data was collected from 387 households using structured question questionnaires, focus group discussions, key informant interviews and document reviews. Descriptive and chi square analysis were employed to analyze the data. Results showed strong relationship between knowledge of the departments tasked to coordinate watershed management activities and the level of food security at household level p<0.001. High variation among the households’ food security status and knowledge of the county environmental protection policy, water services provision policy at p-value=0.000. Watershed management plans and policies did not develop synergy. Thus, there is need for decentralization to strengthen details on watershed governance for sustainable food security in the river basin.